1985
DOI: 10.1111/j.1502-3931.1985.tb00701.x
|View full text |Cite
|
Sign up to set email alerts
|

Small shelly fossils and trace fossils near the Precambrian‐Cambrian boundary in the Yukon Territory, Canada

Abstract: In the past an ‘explosion’ in diversity and abundance of small shelly fossils and of trace fossils has served to mark the base of the Cambrian. However, no evidence has been presented to prove that the ‘explosions’ of the two groups were synchronous. We describe small shelly fossils and trace fossils from the same phosphatic limestone beds that indicate that the two events were separate in time. The small shelly fossils are Anabarites trisulcatus, Hyolithellus cf. H. isiticus, Microcornus? sp., Protohertzina a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0
1

Year Published

1992
1992
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(56 citation statements)
references
References 33 publications
2
53
0
1
Order By: Relevance
“…A slope setting is also interpreted for the lithologically similar Sheepbed Formation in the Stratigraphic levels of fossil occurrences based on the present study and reported occurrences from Hofmann et al (1983) Nowlan et al (1985) and Narbonne and Hofmann (1987). …”
Section: Sheepbed Formationsupporting
confidence: 73%
See 2 more Smart Citations
“…A slope setting is also interpreted for the lithologically similar Sheepbed Formation in the Stratigraphic levels of fossil occurrences based on the present study and reported occurrences from Hofmann et al (1983) Nowlan et al (1985) and Narbonne and Hofmann (1987). …”
Section: Sheepbed Formationsupporting
confidence: 73%
“…A terminal Proterozoic age is indicated by: (1) the occurrence of Ediacaran fossils and simple trace fossils in the Blueflower Formation (Hofmann et al, 1983;Narbonne and Hofmann, 1987); (2) the assemblage of small shelly fossils of Early Cambrian age in the Ingta Formation (Nowlan et al, 1985); and (3) the association of complex trace fossils reported from the overlying Vampire Formation (Fig. 4).…”
Section: Wernecke Mountainsmentioning
confidence: 99%
See 1 more Smart Citation
“…11, panel 56), which occurs at the base of the Nemakit-Daldyn Horizon (Missarzhevsky, 1973). Protohertzina was widespread over the entire Siberian Plat- form, and in Kazakhstan, Mongolia, China, the Lesser Himalayas, and western North America (Conway Morris and Fritz, 1980;Missarzhevsky and Mambetov, 1981;Luo et al, 1984;Nowlan et at, 1985;Brasier and Singh, 1987;Hamdi, 1989). In the Maly Karatau , Mountain Shoria, and Mongolia, Proto hertz ina cultrata Missarzhevsky occurs up to the Botomian.…”
Section: Conodontomorphsmentioning
confidence: 96%
“…Many and varied potential criteria for their distinction were suggested, but it was not until the exhaustive review of type specimens by Pemberton and Frey (1982) that the presence or absence of wall linings emerged as the primary ichnotaxobase. This ichnotaxoDownloaded by [North Carolina State University] at 10:43 23 September 2012 base has since been consistently adopted by other authors for distinction between the two (e.g., Ekdale et al, 1984;Nowlan et al, 1985;Clausen and Vilhjalmsson, 1986;Narbonne and Hofmann, 1987;Martino, 1989;GierlowskiKordesch, 1991;Pickerill, 1992;Leszczynski and Uchman, 1993;Miller, 1993;McCann, 1993;Stanley and Pickerill, 1994) thus providing nomenclatural stability. Hence, the normal provisions of the I.C.Z.N.…”
Section: Review Of the Original Descriptionsmentioning
confidence: 93%